A study on the factors affecting stock liquidity. (1st October 2007) - Cheng, Shuenn-Ren
Stock liquidity is one of the most important factors of asset pricing. For instance, investors will request higher premium for low liquidity securities, otherwise, they will request for lower rate of return. The purpose of this study was to analyse and discuss the factors affecting stock liquidity. This study considered firm size, compression of ownership structure, level of information asymmetry, utilisation rate of margin trading, absorbed stocks of investors, and the entire market's liquidity as the factors affecting liquidity. Using the listed companies of Taiwan Stock Exchange Corporation as a sample, this study used regression analysis and time series in undergoing empirical analysis. It discovered that: (1) the firm size is positively related to liquidity, (2) the more scattered ownership structure is, the higher the liquidity will be, (3) the more critical information asymmetry is, the lower the stock liquidity will be, (4) the higher margin trading utilisation is, the higher the stock liquidity will be, (5) the liquidity of an individual stock is positively related to the liquidity of the entire market and (6) the more investor's perceptions are absorbed, the higher the stock liquidity will be. The results of the study can provide informational services to researchers or the Taiwan Stock Exchange Corporation.